2019
DOI: 10.1101/688887
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trisk 95 as a Novel Skin Mirror for Normal and Diabetic Systemic Glucose Level

Abstract: Coping with diabetes requires frequent and even today mostly invasive blood glucose-based monitoring.Partly due to this invasive nature and the associated reduced skin wound healing and increased risk of infection, non-invasive glucose monitoring technologies would represent considerable progress. Edited keratinocytes may enable such a function.To address this hypothesis, we conducted a proteomic screen in the skin by making use of the experimental in vivo mouse model of type I diabetes alongside controls. We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Recently, we reported that high blood glucose increases the intracellular calcium concentrations and consequently results on mitochondrial morphology changes in primary keratinocytes and murine skin. Our data highlight Trisk95 as main player in this mechanism [73]. High glucose condition increases oxidative stress and the production of cellular ROS [74][75][76].…”
Section: Discussionmentioning
confidence: 62%
“…Recently, we reported that high blood glucose increases the intracellular calcium concentrations and consequently results on mitochondrial morphology changes in primary keratinocytes and murine skin. Our data highlight Trisk95 as main player in this mechanism [73]. High glucose condition increases oxidative stress and the production of cellular ROS [74][75][76].…”
Section: Discussionmentioning
confidence: 62%